Xenopus Limb bud morphogenesis. Issue 3 (3rd November 2015) - Keenan, Samuel R.; Beck, Caroline W.
Abstract : Xenopus laevis, the South African clawed frog, is a well‐established model organism for the study of developmental biology and regeneration due to its many advantages for both classical and molecular studies of patterning and morphogenesis. While contemporary studies of limb development tend to focus on models developed from the study of chicken and mouse embryos, there are also many classical studies of limb development in frogs. These include both fate and specification maps, that, due to their age, are perhaps not as widely known or cited as they should be. This has led to some inevitable misinterpretations‐ for example, it is often said that Xenopus limb buds have no apical ectodermal ridge, a morphological signalling centre located at the distal dorsal/ventral epithelial boundary and known to regulate limb bud outgrowth. These studies are valuable both from an evolutionary perspective, because amphibians diverged early from the amniote lineage, and from a developmental perspective, as amphibian limbs are capable of regeneration. Here, we describe Xenopus limb morphogenesis with reference to both classical and molecular studies, to create a clearer picture of what we know, and what is still mysterious, about this process. Developmental Dynamics 245:233–243, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: Limb bud mesenchyme fate maps show progressive emergence of more distal fates over developmental time, and this is dependent on contact with the distal epithelium (AER). Key molecular markers of dorsal mesenchyme, distal epithelium (AER) and posterior distal mesenchyme (ZPA) are localised in the same way as in amniotes. Xenopus limb buds have a transient morphological AER, but this is not true of all amphibians. Xenopus limb buds develop late (compared to amniotes) and the mesenchyme cells most likely originate from the somatopleure. There are some key differences to aminiotes, like the ability of Xenopus limb buds to produce their own retinoic acid.